Symbolic Presentation of the Disease as Colonial Evil in Chinua Achebe’s "The Sacrificial Egg" - Sharma, Prakash (Pragnya Sarathi प्रज्ञा-सारथि, 2024)
This paper critically examines Chinua Achebe’s short story "The sacrificial egg" to expose how the writer uses the disease smallpox symbolically as the evils of colonialism employing postcolonial perspective. It claims that symbolically presenting the example of the degradation caused by the disease in a small coastal market Umuru, the writer sheds light on the devastating consequences of colonialism in the African continent as a whole. As the context was not appropriate to raise voice against colonialism directly, the writer did so by using literary device of symbolism. Following qualitative research design, this paper uses critical, analytical and interpretative methods and justifies its main claim. In the act of the critical analysis of the primary text, the theoretical ideas of post-colonial theorist like Edward Said are applied. Critical scrutiny of the text brings out the evidences that show the resemblances between the evil impact of colonialism and the contamination of smallpox. Both have destroyed the existing beauty and peace; and contaminated the society. Greed guided mentality of the people plays a vital role in both cases. Umuru is the microcosm of the African continent. Essentiality of eradicating the disease from Umuru for peace and prosperity in the story shows the essentiality of freedom of the whole Africa from colonialism for peace and prosperity. Symbolically the message of the importance of freedom is imparted through the story.